The Racial Injustice of Poverty - Mark R. Rank (Washington University Journal of Law & Policy, 1999)
Professor Roberts’ conclusion is that we should be attacking poverty to improve the well-being of children. In order to shed more light on this, I would like to briefly discuss some of the research on which I am currently working that looks at the issues of poverty and race in a different fashion. My recent work attempts to paint a much broader view of poverty by looking at childhood and adulthood as a whole. Rather than asking what the rate of poverty is at a single point in time in a child’s or adult’s life, the question I am analyzing is: What is the likelihood of poverty across the entire span of the childhood and adulthood years?
Keywords: Poverty; Race discrimination